Barriers to Expanding the National Health Insurance Membership in Indonesia: Who Should the Target? - Agung Dwi Laksono; Zainul Khaqiqi Nantabah; Ratna Dwi Wulandari; Abu Khoiri; Minsarnawati Tahangnacca (SAGE Publishing, 2022)
Background: The Indonesian government initiated National Health Insurance (NHI) to reduce health service barriers. The study aimed to analyze specific targets for expanding the NHI's membership in Indonesia. Methods: The study population was all populations in Indonesia. Meanwhile, the study involved a 47 644 weighted sample. The analyzed variables included NHI's membership, residence, age, gender, education, employment, marital status, and wealth. The study employed binary logistic regression in the final step. Results: The urban population was 0.608 times less likely than the rural population to become a non-member of NHI. Aging younger was one of the barriers to becoming an NHI member, and the male gender is one of the barriers to becoming an NHI member. Meanwhile, the lower the education level, the greater the obstacles to becoming an NHI member in Indonesia. Besides, the unemployed population was 1.002 more likely than the employed population to become a non-member of NHI. The result shows that never married or married have a higher chance of becoming a non-member of NHI. Finally, all wealth status categories are more likely to become barriers to the most prosperous population becoming an NHI member. Conclusions: The study concluded that 7 population characteristics become specific targets for expanding NHI membership in Indonesia. The 7 characteristics are the population who live in rural areas, are young, male, poor education, unemployed, never married or married, and poor.